Anticancer activity of a 1, 4-dihydropyridine in DMBA-induced mouse skin tumor model. Issue 4 (April 2020) - Manna, Debashri; Akhtar, Shabnam; Maiti, Pragati; Mondal, Samiran; Kumar Mandal, Tapan; Ghosh, Rita
Abstract : Antitumor potential of a 1, 4-dihydropyridine derivative (DHP-8) has been successfully studied previously in a number of cancer cell lines including the human melanoma cells, A375. In order to validate its anticancer activity, DMBA induced tumor in Swiss Albino mice was considered for this study. DMBA causes skin carcinoma in murine systems and is an important in vivo model for evaluating the efficacy of any new chemical entity against skin cancer. Topical administration of DHP-8 at the dose rate of 33.3 and 50.0 mg/kg body weight showed a significant reduction in tumor parameters. It also prevented the progression and differentiation of squamous cell carcinoma, as evidenced from histopathological studies. Immunohistochemical analysis for the expression of Ki67 indicated that it also reduced cancer cell proliferation. Additionally, it induced apoptosis in the tumor cells by activation of Caspase3. Our results indicated that DHP-8 efficiently attenuated DMBA induced tumor progression and it could be a potent therapeutic agent for skin cancer treatment.